2018
DOI: 10.1029/2018gl080693
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Ducting of Pc1 Pulsations Observed by Swarm Satellites and Multiple Ground Networks

Abstract: Low Earth orbit satellites frequently encounter Pc1 pulsations, but most have been observed with limited latitudinal extent or short lifetime. In this study we analyze two large‐scale Pc1 pulsations (both latitudinally wide and long‐lasting) generated by ionospheric ducting effect using Swarm and ground magnetometers on 25 June and 3 September 2015. Swarm observed the 25 June pulsations on both dayside and nightside during the storm time substorm (a strong geomagnetic storm on 23 June with Dst =  − 204 nT). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 62 publications
1
38
1
Order By: Relevance
“…We generally follow the data processing scheme described by Kim, Hwang, Park, Bortnik, et al (2018), Kim, Hwang, Park, Miyashita, et al (2018), and Kim et al (2020), which are only briefly summarized here. We used a second‐order Savitzky‐Golay smoothing filter to define the respective backgrounds of both the magnetic field and electron density of Swarm.…”
Section: Data Descriptionmentioning
confidence: 99%
“…We generally follow the data processing scheme described by Kim, Hwang, Park, Bortnik, et al (2018), Kim, Hwang, Park, Miyashita, et al (2018), and Kim et al (2020), which are only briefly summarized here. We used a second‐order Savitzky‐Golay smoothing filter to define the respective backgrounds of both the magnetic field and electron density of Swarm.…”
Section: Data Descriptionmentioning
confidence: 99%
“…(1993) reporting local FLR frequencies in ground‐based magnetometer data at L ≳ 1.5 with frequencies from 66 to 84 mHz. In situ satellites in polar low‐Earth orbit (LEO), such as those from the ESA Swarm constellation, have observed Hertz frequency waves at midlatitudes and high latitudes (e.g., Kim et al., 2018), but these are usually associated with a higher altitude driver such as the growth of electromagnetic ion cyclotron waves which are excited in the equatorial plane and then propagate along field lines to the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Hendry et al (2016) observed precipitation of MeV electrons and keV protons, along with ground‐based EMIC waves, lasting 10 hr in a localized duskside region. However, due to propagation and ducting effects, EMIC waves, particularly those in the H+ frequency band, are not always observed on the ground when and where they occur in space (e.g., Engebretson et al, 2008; Greifinger & Greifinger, 1968; Kim et al, 2018; Posch et al, 2010); thus, in situ observations are needed for estimating spatial and temporal scales of EMIC wave source regions to determine the net impact of these waves on ion and electron dynamics in the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%